2019
DOI: 10.3390/atmos10110696
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of the Spatiotemporal Distribution of Ozone Induced by Cut-Off Lows in the Upper Troposphere and Lower Stratosphere over Northeast Asia

Abstract: This paper presents the results of a statistical study of the spatiotemporal distribution of ozone in the upper troposphere and lower stratosphere (UTLS) regions induced by cut-off lows (COLs) over Northeast Asia. The analysis was based on high-resolution ERA-Interim ozone data and Atmospheric Infrared Sounder (AIRS) satellite data for the period from 2005–2015. A total of 186 COL events were detected. The observed ozone distribution revealed an ozone-rich region in the upper troposphere (300 hPa) located arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The ozone layer absorbs ultraviolet radiation from the Sun and protects the surface biosphere from damaging radiation. Atmospheric fluctuations in the troposphere are uploaded to the stratosphere (Shepherd, 2002;Xie et al, 2012;He et al, 2020a,b;Yu et al, 2020), leading to the abnormal distribution of ozone in the stratosphere (Chen et al, 2019) and affecting the Earth's climate (Bian et al, 2013;Lu and Ding, 2013;Xie et al, 2016;Li et al, 2017). Some anthropogenic ozone-depleting substances (ODSs), such as chlorofluorocarbons (CFCs) and halons, may also be transported to the stratosphere and influence the stratospheric ozone, while stratospheric ozone may transport to the troposphere and influence the tropospheric ozone (Elliot and Rowland, 1987;Schauffler et al, 1999;Butchart and Scaife, 2001;Newman et al, 2009;Oram et al, 2017;Wang et al, 2019Wang et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…The ozone layer absorbs ultraviolet radiation from the Sun and protects the surface biosphere from damaging radiation. Atmospheric fluctuations in the troposphere are uploaded to the stratosphere (Shepherd, 2002;Xie et al, 2012;He et al, 2020a,b;Yu et al, 2020), leading to the abnormal distribution of ozone in the stratosphere (Chen et al, 2019) and affecting the Earth's climate (Bian et al, 2013;Lu and Ding, 2013;Xie et al, 2016;Li et al, 2017). Some anthropogenic ozone-depleting substances (ODSs), such as chlorofluorocarbons (CFCs) and halons, may also be transported to the stratosphere and influence the stratospheric ozone, while stratospheric ozone may transport to the troposphere and influence the tropospheric ozone (Elliot and Rowland, 1987;Schauffler et al, 1999;Butchart and Scaife, 2001;Newman et al, 2009;Oram et al, 2017;Wang et al, 2019Wang et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that, on average, COLs induced a 32% increase of O 3 in the UTLS region. Combining multiyear satellite and reanalysis data, Chen et al (2019) performed another statistical investigation on the spatiotemporal change of UTLS O 3 induced by COLs 95 over the Northeast Asia region. Their statistical results indicated that the magnitude and distribution of ozone enhancements were closely related to the evolution of COLs lifecycle.…”
mentioning
confidence: 99%